Radiotherapy for extensive-stage small-cell lung cancer in the immunotherapy era - Li, Huanhuan; Zhao, Yangzhi; Ma, Tiangang; Shao, Hao; Wang, Tiejun; Jin, Shunzi; Liu, Zhongshan (Frontiers in Immunology, 2023)
Currently, chemoimmunotherapy is the first-line treatment for extensive-stage small-cell lung cancer (ES-SCLC). However, only 0.8%–2.5% of the patients presented complete response after chemoimmunotherapy. Considering that ES-SCLC is highly sensitive to radiotherapy, the addition of radiotherapy after first-line treatment for ES-SCLC could further improve local control, which may be beneficial for patients’ survival. Prior studies have shown that consolidative thoracic radiotherapy (cTRT) can decrease disease progression and improve overall survival in patients with ES-SCLC who respond well to chemotherapy. However, the efficacy and safety of cTRT in the immunotherapy era remain unclear owing to a lack of prospective studies. Prophylactic cranial irradiation (PCI) has been shown to decrease brain metastasis (BM) and prolong survival in patients with limited-stage SCLC in previous reports. However, according to current guidelines, PCI is not commonly recommended for ES-SCLC. Immunotherapy has the potential to reduce the incidence of BM. Whether PCI can be replaced with regular magnetic resonance imaging surveillance for ES-SCLC in the era of immunotherapy remains controversial. Whole brain radiation therapy (WBRT) is the standard treatment for BM in SCLC patients. Stereotactic radiosurgery (SRS) has shown promise in the treatment of limited BM. Considering the potential of immunotherapy to decrease BM, it is controversial whether SRS can replace WBRT for limited BM in the immunotherapy era. Additionally, with the addition of immunotherapy, the role of palliative radiotherapy may be weakened in patients with asymptomatic metastatic lesions. However, it is still indispensable and urgent for patients with obvious symptoms of metastatic disease, such as spinal cord compression, superior vena cava syndrome, lobar obstruction, and weight-bearing metastases, which may critically damage the quality of life and prognosis. To improve the outcome of ES-SCLC, we discuss the feasibility of radiotherapy, including cTRT, PCI, WBRT/SRS, and palliative radiotherapy with immunotherapy based on existing evidence, which may offer specific prospects for further randomized trials and clinical applications.